Implementasi Geografic Information System (GIS) untuk Menentukan Kantor Cabang Imaba Jabodetabek dengan Menggunakan Metode Location Based Service (LBD) Berbasis Android (Studi Kasus: Ikatan Mahasiswa Bata-Bata Jabodetabek) - Zakaria, Hadi; Ghufroniyah, Muflihatul (Jurnal Informatika Universitas Pamulang, 2023)
Imaba Jabodetabek is one of the organizations consisting of Bata-Bata alumni who have been active since 2009. Imaba has several branch offices in Jabodetabek. Not only alumni members but there are also sympathizing members, sympathizing members are alumni from other pesantren who join to become Imaba members. Imaba Jabodetabek now has several branch offices spread across the Jabodetabek area. However, there are obstacles experienced by Imaba Jabodetabek members. When alumni, new members and guests who want to visit the Jabodetabek imaba office find it difficult to find the location of branch offices spread across Jabodetabek. So that alumni, new members and guests are often late when attending events at Imaba Jabodetabek. To make it easier to find the location of Imaba branch offices in Jabodetabek. In this study the authors aim to implement a Geograohic Information System (GIS) using the Location Based Service (LBS) method using android studio, as well as a MySQL database as data storage for branch office search reports as well as road data and other information. And the author uses the RAD method in making the design flow. It is hoped that the creation of this android-based Geographic Information System application can make it easier for Imaba alumni, new members and Imaba guests to find information on the location of branch offices and also the contacts of each branch office located in the Jabodetabek area.